2009
DOI: 10.1007/s11661-009-9809-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Microstructure with Hardness, Wear Resistance, and Corrosion Resistance of Powder-Injection-Molded Specimens of Fe-Alloy Powders

Abstract: In this study, the powder injection molding (PIM) process was applied to Fe-alloy powders. Microstructure, hardness, wear resistance, and corrosion resistance of the PIM specimens were analyzed and compared with those of a conventional stainless steel, SS316L. When Fe-alloy powders were injection molded and then sintered at 1200°C or 1250°C, completely densified specimens with almost no pores were obtained. They contained 63 to 80 vol pct of hard (Cr,Fe) 2 B dispersed in the austenite or martensite matrix. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
2
10
0
1
Order By: Relevance
“…The bulk hardness of M3 specimen was decreased because of the weld dilution that reduced the B concentration and hence reduced the boride particles volume fraction ( Table 2). This finding is consistent with previous studies [2,3,29], which have shown that as the B content increases, the fraction of the hard boride phase increases and consequently the bulk hardness increases. It should be noted that the hardness of the boride particles did not change with the heat input variation.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The bulk hardness of M3 specimen was decreased because of the weld dilution that reduced the B concentration and hence reduced the boride particles volume fraction ( Table 2). This finding is consistent with previous studies [2,3,29], which have shown that as the B content increases, the fraction of the hard boride phase increases and consequently the bulk hardness increases. It should be noted that the hardness of the boride particles did not change with the heat input variation.…”
Section: Resultssupporting
confidence: 93%
“…It is hence concluded that the dark-contrast particles (b and b 0 ) correspond to boride of Cr and Fe phase of the type M 2 B and the light-contrast matrix corresponds to a BCC solid solution of Fe, Cr, Mn, and Si. For similar Fe-Cr-B-based alloys, it has been reported the boride phase particles as (Cr,Fe) 2 B [2,3]. The formation of the BCC solid solution phase is also consistent with the reported results [2,5,6,[9][10][11]14].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Since these cast rods were not sufficiently homogenized, they were held at 1200 1C for 30 min and then cooled in a vacuum furnace. This heat-treatment condition was same to the sintering condition of the PIM process [16].…”
Section: Casting and Heat Treatment Of Fe-based Pim Alloysmentioning
confidence: 99%
“…For example, conventional stainless steel powders used for the PIM include STS 304L, 316L, 430, and 630 powders [12][13][14][15]. Recently, PIM parts were fabricated with hard Fe-based alloy powders (composition; Fe-43Cr-5.6B-1.8Si-0.2S-0.17C (wt%)) which is called as Armacor TM 'M' (commercial brand name of the Liquidmetal Technologies, Lake Forest, CA, USA) [16]. These parts showed much higher hardness, corrosion resistance, and wear resistance than those fabricated with conventional stainless steel powders.…”
Section: Introductionmentioning
confidence: 99%